2015
DOI: 10.1371/journal.pone.0132701
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Activity of the Plant Defensin HsAFP1 and Caspofungin against Candida albicans Biofilms and Planktonic Cultures

Abstract: Plant defensins are small, cysteine-rich peptides with antifungal activity against a broad range of yeast and fungi. In this study we investigated the antibiofilm activity of a plant defensin from coral bells (Heuchera sanguinea), i.e. HsAFP1. To this end, HsAFP1 was heterologously produced using Pichia pastoris as a host. The recombinant peptide rHsAFP1 showed a similar antifungal activity against the plant pathogen Fusarium culmorum as native HsAFP1 purified from seeds. NMR analysis revealed that rHsAFP1 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 82 publications
4
67
0
6
Order By: Relevance
“…In that study, recombinant HsAFP1 was shown to act synergistically with caspofungin in the prevention and eradication of C. albicans biofilms [53]. Such synergistic antibiofilm activities between plant defensins and conventional antimycotics are not defensin-specific.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…In that study, recombinant HsAFP1 was shown to act synergistically with caspofungin in the prevention and eradication of C. albicans biofilms [53]. Such synergistic antibiofilm activities between plant defensins and conventional antimycotics are not defensin-specific.…”
Section: Discussionmentioning
confidence: 92%
“…We recently reported on the antibiofilm activity of another plant defensin, HsAFP1, which can inhibit C. albicans biofilm formation, but cannot eradicate C. albicans biofilms [53]. In that study, recombinant HsAFP1 was shown to act synergistically with caspofungin in the prevention and eradication of C. albicans biofilms [53].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations